Impacts of an Is on productivity and job satisfaction – healthcare and retail - Silva, F.; Oliveira, A. (Mediterranean Journal of Social Sciences, 2014)
The information systems are useful tools to get better performance to organizations and their employees. Other relevant factors to achieve a good organizational performance are having good levels of productivity, and a high level of job satisfaction - with employees that effectively are identified with a company and its goals. These aspects are very relevant to the business areas of health and retail, due to the strategic objectives defined primarily in terms of budget, quality of services assurance, and, in the case of the retail sector, due to competitiveness. Companies acquire information systems to increase their organizational performance. This study analyses the perception of impacts that an information system promotes on organizations, in terms of levels of productivity and job satisfaction, according to the perspective of employees in the Human Resources department, and managers in the areas of health and retail. A questionnaire was administered to 113 users of the application, and it was found that, after using that software for some time, they consider themselves more productive (than satisfied) at work and, in general, they recognize several benefits to justify the use of the application, especially in terms of their productivity, feeling in general satisfied. The performance improvements, the correct application of legislation, and the process optimization, contribute to improve communication and to increase the quality of life of employees. These are the main impacts recognized by users of the application, so it appears that these improvements provide greater levels of productivity and greater job satisfaction.